(untitled) (Research, Society and Development, 2025)
This study aimed to describe the practical experience of Food and Nutrition Education for adolescents, carried out through an intervention with students from the public school system. This is a descriptive study of the type of experience report on the experiences of students from the Nutrition course at Salvador University (UNIFACS), during the implementation of EAN actions in the context of the National School Feeding Program, with adolescents from elementary school classes II, in a school located in the state of Bahia. The practices were defined by nutritional diagnosis information extracted from the Food and Nutrition Surveillance System - SISVAN, in the context of a public policy. These actions were carried out using a free, digital technological product, created in the format of a magazine with themes such as the importance of fruit consumption for health and the main nutrients considered to be allies of growth. Finally, a simple questionnaire was used to collect qualitative information about the performance of the technological product. The results achieved with the intervention were satisfactory and showed that EAN tools encourage and guide adolescents to change their habits effectively.